Poisoned for Pennies: The Economics of Toxics and Precaution - Ackerman Frank (Island Press, 2008)
“Cost-benefit analysis” is a term that is used so frequently we rarely stop to think about it. But relying on it can lead to some dubious conclusions, as Frank Ackerman points out in this eye-opening book. For example, some economists have argued that states should encourage—and even subsidize—cigarette smoking by citizens because smoking will shorten life spans and therefore reduce the need and expense of caring for the elderly. How did the economists reach that conclusion? The answer is cost-benefit analysis, Ackerman explains.